Three Interesting Properties of Metallic Ratios - SIVARAMAN, DR. R. (The journal of contemporary issues in business and government, 2021)
The study of Metallic ratios has profound impact and applications not just in mathematics but also in various other branches of Science and Technology. In this paper, I will introduce the Metallic Ratios formally and prove three interesting and new properties related to them. These results will add more value to already known results on Metallic Ratios.